2021
DOI: 10.1002/cbic.202100344
|View full text |Cite
|
Sign up to set email alerts
|

Photoactivation of Innate Immunity Receptor TLR8 in Live Mammalian Cells by Genetic Encoding of Photocaged Tyrosine

Abstract: The effectiveness of innate immune responses relies on an intricate balance between activation and regulation. TLR8, a member of the Toll‐like receptor (TLR) family, plays a fundamental role in host defense by sensing viral single‐stranded RNAs (ssRNAs). However, the molecular recognition and regulatory mechanism of TLR8 is not fully understood, especially in a whole‐cell environment. Here, we engineer the first light‐controllable TLR8 model by genetically encoding a photocaged tyrosine, NBY, into specific sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…Therefore, the decreased transcript levels of tlr9 and tlr13 may be a protection measure to enhance the mucosal barrier and attenuate intestinal injury and inflammatory responses under transport stress. The inconsistent patterns of tlr5 , tlr9 , and tlr13 transcript accumulation under transport stress were considered to reflect the effectiveness of the innate immune response, with its intricate balance between activation and regulation [ 42 ]. In another study, the down-regulation of syngr3 , which encodes a synaptic vesicle protein, was found to alleviate synaptic dysfunction in mouse and fruit fly primary neurons [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the decreased transcript levels of tlr9 and tlr13 may be a protection measure to enhance the mucosal barrier and attenuate intestinal injury and inflammatory responses under transport stress. The inconsistent patterns of tlr5 , tlr9 , and tlr13 transcript accumulation under transport stress were considered to reflect the effectiveness of the innate immune response, with its intricate balance between activation and regulation [ 42 ]. In another study, the down-regulation of syngr3 , which encodes a synaptic vesicle protein, was found to alleviate synaptic dysfunction in mouse and fruit fly primary neurons [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral blood mononuclear cell (PBMC) were isolated from murine whole blood with Ficoll reagent following the previously established protocols ( 42 ).…”
Section: Methodsmentioning
confidence: 99%